(untitled) (Lex localis - Journal of Local Self-Government, 2010)
This article compares local government reforms in three European countries: France, the United Kingdom (England), and Germany. In the analysis, the author distinguishes between two different types of reform. Firstly, the vertical dimension of the reform refers to the decentralisation of public tasks from the state/central government to local authorities. Secondly, in an illustration of the horizontal dimension, the readjustment of competencies between local authorities and market or non-profit actors is investigated by focusing on the development of privatisation, corporatisation, and contracting out. The paper pursues the following questions: What effects did the decentralisation and privatisation processes cause in the three countries, and did they contribute to performance improvements at the local level? The author reveals that the anticipated positive outcomes of the reforms have proven to be only partially accurate, and that in many cases unexpected and even rather negative consequences have resulted instead.